The Sámi of Jokkmokk: Challenging modernity - Marie Roué (The UNESCO Courier, 2019)
The territory in Swedish Lapland, where the indigenous Sámi raise their reindeer, is threatened by logging, the railway, dams and urban growth. To survive, the herders have adopted a variety of strategies that range from the partial adaptation of an urban lifestyle, to using their traditional knowledge to accurately understand the state of their pastures.